Territorial Public Finances in Colombia - Rodríguez Araújo, Edilberto ; Universidad Pedagógica y Tecnológica de Colombia; Vallejo Zamudio, Luis Eudoro ; Universidad Pedagógica y Tecnológica de Colombia; Cruz Vásquez, José Luis; Universidad Pedagógica y Tecnológica de Colombia; Medina Miranda, Rolando ; Universidad Pedagógica y Tecnológica de Colombia; Gil León, José Mauricio; Universidad Pedagógica y Tecnológica de Colombia; Casas Herrera, Julián Augusto ; Universidad Pedagógica y Tecnológica de Colombia; Mora Toscano, Oliver Marcel; Universidad Pedagógica y Tecnológica de Colombia; Cárdenas Salinas, José Miguel; Universidad Pedagógica y Tecnológica de Colombia; González Borrero, Jorge Iván; Universidad Nacional de Colombia; Barrios Ordóñez, Jesús Fernando; Universidad Javeriana; Bonilla González, Ricardo; Universidad Nacional de Colombia; Romero Bolívar, Fabián Leonardo; Universidad Pedagógica y Tecnológica de Colombia; et al. (UPTC Editorial, 2021)
Since the mid-eighties, when the decentralization process began in Colombia, relations between the different territorial entities and the central government have been characterized by permanent tensions in which the demands for greater autonomyand discretion in spending capacity that is financed with transfers from the General Participation System (SGP) and the General Royalties System (SGR) have not been absent.There is no doubt that the distribution of powers and the allocation of additional resources to subnational governments have contributed to the economic growth and social development of municipalities and states; however, interregional disparitiesand horizontal inequity persist in access to public goods. Notwithstanding the State payments have increased, the fiscal effort of the territorial governments has not been less, which have increased their own resources and their concomitantefficiency, in the search to underpin local and regional development.The occurrence of an unexpected phenomenon, such as the pandemic unleashed by COVID-19 in March 2020, caused not only a health crisis to erupt, but also an economic and social crisis, which led to the implementation of strategies to avoid its spread and facilitate its containment and mitigation. This situation affected territorial finances since there was a drop in tax collection and pressure on social spending that accentuated recurring budget losses in the country. Post-pandemic will find empty state coffers and enormous commitments to reverse the deterioration of the social indicators of the country’s municipalities and states.